Does school climate matter in cyberbullying behaviour among high school student? A mediation and moderation analysis - Maftuh, Bunyamin; Dahliyana, Asep; Malihah, Elly; Sartika, Rika (Jurnal Cakrawala Pendidikan, 2024)
Information technology development has had positive and negative impacts on the education sector. One of the negative impacts is the emergence of new bullying behaviour by utilizing information technology online or cyberbullying behaviour. Previous studies have examined that cyberbullying is often associated with school climate, psychological capital, and social media addiction. However, until now, limited studies still discuss mediation and moderation relationships between school climate factors, psychological capital, social media addiction, and student cyberbullying behaviour. This study involved 384 high school students from six public and private high schools in Magelang, Indonesia. The study's results explain that cyberbullying behaviour is influenced by school climate and students' psychological capital. Psychological capital is positively influenced by school climate. In addition, psychological capital has successfully mediated the effects of school climate on high school students' cyberbullying behaviour. And finally, social media addiction is proven to moderate the effects of school climate and high school students' cyberbullying behaviour.